Diagnosis of Endometriosis Biomarkers and Clinical Methods - Laganà, Antonio Simone (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Endometriosis is defined as the presence of endometrial-like endometrial cells, glands, and stroma outside the uterus, causing a wide range of symptoms and signs, including acute and chronic pelvic pain and infertility. Endometriosis affects approximately 10% of women of reproductive age, and up to 50% of infertile women. The etiopathogenesis of endometriosis still remains controversial: immune, hormonal, genetic, and epigenetic factors may be all involved, and several theories have been proposed to explain it.One of the main problems for the management of endometriosis is the significant diagnostic delay: to date, several biomarkers are currently being tested in order to provide a reliable non-invasive diagnosis in case of symptoms and signs suspicious for endometriosis.In addition, ultrasound techniques and magnetic resonance imaging are evolving rapidly, allowing for better accuracy, even with the use of artificial intelligence. Finally, new potential histological makers are helping to correlate the occurrence of endometriosis in different anatomical landmarks, supporting specific pathways to clarify the etiology of the disease.